French Language Education Students' Perceptions Of Career Opportunities In The Tourism And Hospitality Sectors - Jasmine Naizura; Iim Siti Karimah; Yadi Mulyadi (Politeknik Internasional Bali, 2026)
The French language is the sixth most widely used language globally, and proficiency in it is essential in the growing international tourism and hospitality sectors, where effective foreign language communication is highly demanded. However, students in the French Language Education Study Program are primarily prepared for careers as educators, despite preliminary data indicating a strong preference among graduates for non-education sectors, specifically tourism and business. This study addresses a significant research gap by exploring how French Language Education students with their unique linguistic and cultural mastery perceive career opportunities in the tourism and hospitality industry. This research aimed to identify these perceptions, analyze influencing factors, and assess students' career readiness outside the education sector. Employing a qualitative descriptive method, data were collected from sixth to eighth semester students specializing in Français sur Objectifs Spécifiques (FOS) using semi-structured interviews and analyzed with the Miles and Huberman model. The findings reveal that students generally hold positive perceptions of career opportunities, driven by external factors such as the increasing number of foreign tourists and high earnings potential as well as internal factors including strong confidence in French proficiency and the influence of FOS-related courses. Main barriers identified include a lack of specialized training and limited practical experience. The study concludes that students possess a strong, informed understanding and generally high readiness for non-education careers, suggesting a need for a curriculum that integrates multilingual vocational preparation and fieldwork to enhance global competitiveness and support the tourism workforce.